The Effect of Dice-Based Reading Media on Early Literacy Skills of Children - Imroatus Syafiqoh (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
Early reading skills constitute a critical foundation for literacy development in early childhood. Despite their importance, early reading instruction at the ECE (Early Childhood Education) level often relies on conventional methods that are insufficiently engaging, resulting in low motivation and limited skill acquisition. This study aimed to investigate the effect of using reading dice media on the early reading abilities of young learners. A quantitative pre-experimental design with a one-group pretest-posttest model was employed. The participants were a cohort of early childhood children at ECE 05 Bahrul Ulum Lamongan. Early reading skills, including letter recognition, syllable decoding, and simple word reading, were assessed using standardized observation sheets. Descriptive statistics, including mean and standard deviation, were used to analyze the data. The results indicated significant improvements in early reading abilities following the implementation of reading dice, accompanied by increased engagement, enthusiasm, and participation in learning activities. These findings suggest that reading dice provide an effective, play-based instructional medium that facilitates early reading acquisition and enhances learner motivation. The study contributes to the development of innovative instructional strategies in early childhood education, particularly in contexts requiring active and interactive learning approaches.